(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2008)
Individuals with developmental disabilities usually show delay in their speech development, so they use alternative communication procedures with visual stimulus like PECS (Picture Exchange Communication System). This study shows the results from two independent researches that investigated the efficacy of PECS and its collateral effects over verbalization frequency and over other specific behaviors (keeping eye contact and sit down during activities for P1; and go up and down stairs for P2). P1, 11 years old, was diagnosed with Fragile X Syndrome with autistic characteristics; and P2, 23 years old, has Down Syndrome. Data showed that P2 learned the first phase of PECS faster than P1. Verbalization frequency was increased and concrete and structured characteristics of the training contributed to increase the frequency of other behaviors.